The Poisson—Jensen formula with the double integral - Kabaila, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Кабайла. Аналог формулы Пуассона — Йенсена с двойным интеграломV. Kabaila. Puasono—Jenseno formulės analogas su dvilypiu integralu